2018
DOI: 10.2174/1568026618666180427145308
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Proteasome System as a Potential Drug Target for Malaria

Abstract: Parasites of Plasmodium genus are responsible for causing malaria in humans. Resistant strains to all available antimalarials can be found in several locations around the globe, including parasites resistant to the latest generation of combination drugs, such as piperaquine + artemisinin. Plasmodium develops between two completely different hosts such as a vertebrate one and the mosquito vector, thus it has the ability to adapt to very extreme and different environments. Through the complex life cycle in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Although the precise mechanisms associated with the role of HBx in viral infection remain to be understood, the reviewed studies support that modulation of the host UPS by HBx plays an important role in regulating HBV replication and the pathogenesis of liver diseases, especially HCC. Significant progress has been made in identifying the molecules that target specific UPS components as a potential target for different disease therapies [99101]. A further understanding of the complicated interactions between the HBV and the host UPS, particularly the HBx-UPS interaction, could provide novel insight into the mechanisms of viral pathogenesis, and help determine potential therapeutic strategies involving targeting the UPS to block HBV infection and associated liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanisms associated with the role of HBx in viral infection remain to be understood, the reviewed studies support that modulation of the host UPS by HBx plays an important role in regulating HBV replication and the pathogenesis of liver diseases, especially HCC. Significant progress has been made in identifying the molecules that target specific UPS components as a potential target for different disease therapies [99101]. A further understanding of the complicated interactions between the HBV and the host UPS, particularly the HBx-UPS interaction, could provide novel insight into the mechanisms of viral pathogenesis, and help determine potential therapeutic strategies involving targeting the UPS to block HBV infection and associated liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The reversible, covalent peptide boronate proteasome inhibitors bortezomib and ixazomib are used clinically to treat multiple myeloma. Ixazomib is administered orally and offers a favorable efficacy/safety profile with weekly dosing delivered as a fixed dose. , Bortezomib has been shown to have activity against P. falciparum , ,, although it has not been formally demonstrated that this results from inhibition of the P. falciparum proteasome. In this work, we used in vitro directed evolution to generate bortezomib-resistant parasites, thereby validating the β5 subunit of the proteasome as the target.…”
Section: Introductionmentioning
confidence: 99%
“…This process is a component of the ubiquitin-proteasome system (UPS) that regulates protein turnover in cells [14]. There are hundreds of enzymes involved in the addition (Ub ligases) or removal (Ub hydrolases) of ubiquitin, and the UPS has emerged as an important source of drug targets in many diseases [15][16][17][18][19][20]. Deubiquitinases (DUBs) are Ub hydrolases responsible for the removal of Ub PTMs by cleaving the isopeptide bond between the C-terminal glycine of Ub and surface lysine residues on target proteins [14].…”
Section: Introductionmentioning
confidence: 99%